A systematic approach to the recurrent laryngeal nerve dissection at the cricothyroid junction - Oleksandr Butskiy; Brent A. Chang; Kimberly Luu; Robert M. McKenzie; Donald W. Anderson (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background To describe and evaluate a four step systematic approach to dissecting the recurrent laryngeal nerve (RLN) starting at the cricothyroid junction during thyroid surgery (subsequently referred to as the retrograde medial approach). Methods All thyroidectomies completed by the senior author between August 2014 and January 2016 were retrospectively reviewed. Patients were excluded if concurrent lateral or central neck dissection was performed. A follow up period of 1 year was included. Results Surgical photographs and illustrations demonstrate the four steps in the retrograde medial approach to dissection of the RLN in thyroid surgery. Three hundred forty-two consecutive thyroid surgeries were performed in 17 months, including 213 hemithyroidectomies, 91 total thyroidectomies, and 38 completion thyroidectomies. The rate of temporary and permanent hypocalcemia was 13% (95% confidence interval [CI]: 8–20%) and 3% (95% CI: 1–8%) respectively. The rate of temporary and permanent vocal cord palsy was 9% (95% CI: 6–12%) and 0.3% (95%CI: 0.01–2%) respectively. The median surgical times for hemithyroidectomy, total thyroidectomy, and completion thyroidectomy were 39 min (Interquartile range [IQR]: 33–47 min), 48 min (IQR: 40–60 min), and 40 min (IQR: 35–51 min) respectively. 1% of cases required conversion to an alternative surgical approach. Conclusion In a tertiary endocrine head and neck practice, the routine use of the retrograde medial approach to RLN dissection is safe and results in a short operative time, and a low conversion rate to other RLN dissection approaches.